Quo vadit psychologia: a philosophia vel ad philosophiam? - Todorović, Milorad V (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Where is psychology heading: away from philosophy or towards it? It seems that psychology itself had to thematize, inter alia, both scope and consequences of its “separation and individuation” from philosophy and its own philosophical sources. Instead of having a philosophical context, within which the previous psychological knowledge existed, the contemporary psychology has been left to metaphysics, meta-technique and mathematization for the purposes of its growth as an empirical science, i.e. the purposes of extolling the basic scientific postulates in the scientific method domain; and it has thus lost both its “soul” and the soul as a proper object of study. Its avoidance to use the word “soul” might be the best testimony of this fact. Contemporary psychology – as an essentially anti-philosophical psychology – has placed the “psychological” firmly in the physical, otorhinolaryngological or ophthalmological content, researching mostly only simple empirical relations. Such a psychology goes against its proper interests precisely because its anti-philosophical orientation reduces its content to a physical fact prepared to enter exclusively mathematical operations. As opposed to that, a psychology maintaining its relationship with philosophy would itself be an experience, instead of a theoretical understanding. In place of psychology focusing on life itself, as Heidegger suggested, and not only sensations, impressions based on touch, and memory factors, what is happening is exactly the opposite. If psychology was to examine life in its entire reality, it certainly wouldn’t be forced to become the true philosophy, but the philosophical approach would only contribute to increased critical and comprehensive nature of psychological research. The manner in which the academic psychology perceives both individual functions and the subject itself provides a sound indicator of these “partial” objects of cognition. Those, in turn, as partial perspectives of psychological knowledge, inevitably lead to a multitude of psychologies. Only philosophy can represent the common denominator containing the need for creation of a unique science which does not imply the reduction of Multitude to One, but instead implies the lack of such theoretical ‘outbursts’ of prejudices against the terms of “mental entities” and “psychic processes” which remain as a heritage of behaviorism. If Gilles Deleuze and Félix Guattari can pose a question about what philosophy is, then the psychologists could pose the same question. Especially since they could receive significant assistance from philosophy “as a skill of notion forming, inventing and production” (according to the teachings of Guattari and Deleuze, among others).